Dynamic insulin sensitivity index: importance in diabetes - Pillonetto, Gianluigi (American Physiological Society, 2010)
The classical minimal model (MM) index of insulin sensitivity, S(I), does not account for how fast or slow insulin action takes place. In a recent work, we proposed a new dynamic insulin sensitivity index, S(I)(D), which is able to take into account the dynamics of insulin action as well. The new index is a function of two MM parameters, namely S(I) and p(2), the latter parameter governing the speed of rise and decay of insulin action. We have previously shown that in normal glucose tolerant subjects S(I)(D) provides a more comprehensive picture of insulin action on glucose metabolism than S(I). The aim of this study is to show that resorting to S(I)(D) rather S(I) is even more appropriate when studying diabetic patients who have a low and slow insulin action. We analyzed insulin-modified intravenous glucose tolerance test studies performed in 10 diabetic subjects and mixed meal glucose tolerance test studies exploiting the triple tracer technique in 14 diabetic subjects. We derived both S(I) and S(I)(D) resorting to Bayesian and Fisherian identification strategies. The results show that S(I)(D) is estimated more precisely than S(I) when using the Bayesian approach. In addition, the less labor-intensive Fisherian approach can still be used to obtain reliable point estimates of S(I)(D) but not of S(I). These results suggest that S(I)(D) yields a comprehensive, precise, and cost-effective assessment of insulin sensitivity in subjects with impaired insulin action like impaired glucose tolerant subjects or diabetic patients.